THE IMPORTANCE OF THE INTEGRATION OF MODERN DIGITAL TECHNOLOGIES AND INTERACTIVE METHODS IN GEOGRAPHY TEACHING - Madraximov Shuxratjon Shukurovich; O‘rinboyeva Adibaxon To‘lanboy qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the integration of modern digital technologies and interactive methods in the teaching of geography. It presents the "Mind Mapping" method and the sequence of making a mind mapping on the topics of the African continent in the EdravMindMaster program.